2008
DOI: 10.1590/s0102-695x2008000500024
|View full text |Cite
|
Sign up to set email alerts
|

Acanthospermum hispidum DC (Asteraceae): perspectives for a phytotherapeutic product

Abstract: RESUMO: "Acanthospermum hispidum DC (Asteraceae): perspectivas para um produto fi toterápico". A planta "Espinho-de-cigano" (Acanthospermum hispidum DC) é amplamente usada no nordeste do Brasil como medicamento popular para a asma. Embora muito pouco seja conhecido atualmente sobre a efi cácia e segurança deste extrato vegetal, é possível encontrar numerosos medicamentos preparados com ele nos serviços públicos ou em lojas que vendem produtos naturais. Este estudo visa proceder a uma revisão de literatura rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(34 reference statements)
1
7
0
2
Order By: Relevance
“…However, the Dd2 strain was not used. Aerial parts of Acanthospermum hispidum have been shown to contain antioxidants, glycosides, coumarins and flavonoids (Araùjo et al 2008). Thereby, the antiplasmodial activity observed in this study might be attributed to one of these compounds since antioxidants, glycosides, coumarins and flavonoids have been reported to possess antimalarial activity (Sriwilaijroen et al, 2010).…”
Section: Discussionsupporting
confidence: 48%
“…However, the Dd2 strain was not used. Aerial parts of Acanthospermum hispidum have been shown to contain antioxidants, glycosides, coumarins and flavonoids (Araùjo et al 2008). Thereby, the antiplasmodial activity observed in this study might be attributed to one of these compounds since antioxidants, glycosides, coumarins and flavonoids have been reported to possess antimalarial activity (Sriwilaijroen et al, 2010).…”
Section: Discussionsupporting
confidence: 48%
“…Acanthospermum hispidum was the subject of several previous studies which showed many biological activities (Araújo et al, 2008). If in vitro antiplasmodial activity was already described with extracts of the plant, and was shown to be higher for a specific extract defined as "alkaloid" extract (Sanon et al, 2003;Bero et al, 2009), it is the first time that sesquiterpenic lactones are clearly related to the activity of this plant.…”
Section: In Vitro Antiplasmodial and Cytotoxic Activitiesmentioning
confidence: 99%
“…Asteraceae é bastante estudada, também devido aos promissores compostos químicos produzidos por este grupo (ARAUJO et al 2008). Bahia (1979) já citava o alumã (Vernonia bahiensis Tol.)…”
Section: Continuaçãounclassified